2019
DOI: 10.33549/physiolres.933907
|View full text |Cite
|
Sign up to set email alerts
|

Differences in serum steroid hormones concentrations in Spontaneously Hypertensive Rats (SHR) – an animal model of Attention-Deficit/Hyperactivity Disorder (ADHD)

Abstract: Spontaneously hypertensive rats are the most common animal model used to study attention deficit hyperactivity disorder (ADHD). The present study investigated the levels of steroid hormones in the bloodstream of hypertensive rats and its normotensive control strain, Wistar-Kyoto rats, to check if there are any hormonal differences between both strains at the onset of ADHD. Plasma samples were collected from young (5-week-old) and mature (10-week-old) male hypertensive and normotensive rats to determine the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…3~6). These behavioral phenotypes are clearly consistent with hyperactivity in ADHD models [19,23]. It is also possible that increased spent time and distance in the center of the OF test and the open arms of the EPM test reflect anxiolytic and impulsive emotion of Corti.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…3~6). These behavioral phenotypes are clearly consistent with hyperactivity in ADHD models [19,23]. It is also possible that increased spent time and distance in the center of the OF test and the open arms of the EPM test reflect anxiolytic and impulsive emotion of Corti.…”
Section: Discussionsupporting
confidence: 63%
“…Recently, it was reported that prenatal stress increases anxiety, depression, and stress-related hyperactive behaviors as well as deficits in learning and memory function [15][16][17][18]. Particularly, spontaneously hypertensive rats (SHRs), which are frequently used in studies of attention deficit hyperactivity disorder (ADHD), showed higher serum levels of progesterone, corticosterone and cortisol than normal rats, suggesting that the endocrine-dependent regulation in developmental nervous system plays a major role in determining behavioral and emotional disorders [19]. However, although neuroendocrine dysregulation has been targeted in studies of psychiatric disorders, it is still necessary to investigate whether maternal stressors during pregnancy directly mediates behavioral and emotional abnormalities in postpartum offspring.…”
Section: Introductionmentioning
confidence: 99%
“…In SHRs, an enhanced lipolysis has been suggested as a result of increased sympathetic outflow; moreover, an increased secretion of cholesterol combined with deficiencies in enteric capture and molecular transport of cholesterol was also demonstrated [ 20 , 21 ]. In addition, it has been shown that the levels of cholesterol-related steroid hormones, such as corticosterone, were elevated already in 7-week-old female SHRs compared to age-matched WKYs, and in 10-week-old SHRs, the serum levels of progesterone, corticosterone, and cortisol were significantly elevated compared to those in 5-week-old SHRs and 10-week-old WKYs [ 16 , 22 ], which may also contribute to the reduction in total cholesterol in our experimental group.…”
Section: Discussionmentioning
confidence: 99%
“…SHR is considered a commonly used and well-studied animal model of ADHD because it exhibits behavioral disorders similar to ADHD in terms of hyperactivity, impulsivity, and learning disabilities, predicts molecular genetics and neuropathological mechanisms associated with ADHD, and responds to first-line ADHD therapeutic agents (Rahi and Kumar, 2021). Since ADHD is more common in boys than in girls, and male rats are superior to females in terms of surface validity (hyperactive/ impulsive behavior), male SHRs are more suitable as an animal model of ADHD (Bayless et al, 2015;Kozłowska et al, 2019). This study attempted to use male SHRs as the ADHD animal model and WKY rats as the normal control to investigate the potential mechanisms of LMQXM for ADHD and explore the effects of LMQXM on behavioral performance and related factors in SHRs.…”
Section: Introductionmentioning
confidence: 99%